Low-Grade Malignant Triton Tumor of the Neck: A Case Report and Review of the Literature - Taissir Omar; Hanaa Raslan; Sahar El Sheikh; Moataz Rizq; Awatef Draz (Case Reports in Pathology)
Rhabdomyoblastic differentiation in a malignant peripheral nerve sheath tumor (MPNST) is termed malignant triton tumor (MTT), a rare neoplasm that poses a diagnostic dilemma in the differential diagnosis of neck masses and portends poor prognosis. We report a sporadic case of MTT of the neck in a 23-year-old female. We present the pathological findings. Immunohistochemistry confirmed the neurogenic origin with S-100 expression and the rhabdomyoblastic differentiation with desmin and vimentin positivity. Radical surgical excision was done. After 4 years there were no signs of recurrence or distant metastasis. The clinical, microscopic, and long-term follow-up of this case are consistent with those of a low-grade malignancy.